Nursing of a pancreatic cancer patient with low back pain treated by massage combined with moxibustion (手法推拿联合生姜开穴施灸治疗1例胰腺癌腰痛患者的护理) - WANG Yudan (王玉丹); WANG Jing (王敬); PAN Yanchun (潘艳春); LI Xiaoying (李晓颖); ZHANG Wenwen (张文文) (中西医结合护理)
This paper investigate the effect of massage combined with moxibustion in treating low back pain in a patient with pancreatic cancer, and summarized related nursing measures. Based on the comprehensive nursing assessment and acupoint selection by syndrome differentiation, the combination of massage and moxibustion treatment were carried, as well as nursing interventions on daily life, diet and mental health of the patient, to relieve the symptoms of cancer-related low back pain and improve the quality of life. (本文总结手法推拿联合生姜开穴施灸治疗1例胰腺癌腰痛患者的护理体会。通过科学评估和辨证取穴, 开展手法推拿联合生姜开穴施灸, 同时配合生活护理、饮食护理、心理护理等, 旨在缓解患者疼痛症状, 提高患者生活质量。)